Methods of wintering steer calves that are to be grazed a full season and sold off of grass. - Smith, E.F.; Good, D.L.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
It is a well known fact that thin steers usually gain more on grass than fleshy steers. However, information is available about the total gain, winter and summer, of steers wintered at different levels and then grazed on bluestem pasture. The primary objective of this test is to determine how steer calves should be wintered that are to be grazed a full season on bluestem pasture and sold off of grass. This is a report on the wintering phase, prior to going to grass for the 1950 season.
Keywords: Beef; Bluestem pasture; Gain